MANUFACTURER PRICE SURVEY RESULTS OF BANK INDONESIA LHOKSEUMAWE WORKING AREA MONTH APRIL 2024 Collaboration between the Bank Indonesia (BI) Lhokseumawe Representative Office and the Faculty of Economics and Business, Malikussaleh University - Muammar Khaddafi; Mohd Heikal; Chalirafi; Munandar; Rico Nur Ilham; T. Edyansyah (RADJA PUBLIKA, 2024)
The development of the Strategic Food Price Information Center (PIHPS) is a real effort from the TPID Pokjanas to facilitate the development of a food information system which also functions as a national scale food price control policy coordination system. PIHPS aims to be a price monitoring tool, policy coordination and a means to expand access to price information for the public. The number of samples of